Smart army robot design as a monitoring and negotiation media based on artificial intelligence - Winardi Maulana; Mokhammad Syafaat; Kasiyanto; Dekki Widiatmoko; Achmad Afif Irwansyah (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Salah satu komponen paling penting dari upaya penyelamatan sandera adalah kesepakatan tentang pembebesan sandera. Kesalahan petugas dalam mengambil tindakan selama proses negosiasi dapat membahayakan keselamatan personel dan petugas serta korban yang disandera. Kurangnya komunikasi sering menyebabkan konflik yang berbahaya yang dapat menghambat penyanderaan. Untuk mengatasi masalah ini, kami merancang robot negosiasi khusus yang dipersenjatai untuk memastikan keselamatan dan keamanan petugas dalam menjalankan tugas, baik dalam situasi perang maupun operasi pembebasan sandera. Dengan memiliki senjata, petugas yang bertanggung jawab atas keselamatan korban dapat melakukan tugas mereka tanpa mengorbankan keamanan pribadi mereka. Robot militer ini memungkinkan negosiasi dan pemantauan tanpa mengancam nyawa, memberikan pendekatan yang lebih efisien dan aman. One of the most important components of hostage rescue efforts is an agreement on hostage release. Mistakes by officers in taking action during the negotiation process can endanger the safety of personnel and officers as well as victims being held hostage. Lack of communication often leads to dangerous conflicts that can hinder hostage taking. To overcome this problem, we designed a special negotiation robot that is armed to ensure the safety and security of officers in carrying out their duties, both in war situations and hostage release operations. By having a weapon, officers responsible for the safety of victims can carry out their duties without compromising their personal safety. These military robots enable negotiation and monitoring without threatening lives, providing a more efficient and safer approach. Additionally, the robot's ability to operate autonomously with the help of artificial intelligence allows for quicker assessment of the situation and more appropriate responses, thereby increasing the chances of success of a rescue mission without increasing risks for the humans involved. The robot is also equipped with advanced sensors and machine learning algorithms that can detect changes in a hostage taker's behavior and body language, providing valuable information to the negotiation team to devise more effective strategies. Thus, the implementation of this technology not only increases the security and efficiency of military operations, but also paves the way for further innovation in the use of robotics and Artificial Intelligence in various aspects of defense and security